2006
DOI: 10.1001/archopht.124.9.1251
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure Variation During Weight Lifting

Abstract: To evaluate the effect of weight lifting on intraocular pressure (IOP). Methods: Subjects performed 4 repetitions of a bench press exercise in 2 ways: in mode I (right eyes), the breath was held during the last repetition; in mode II (left eyes), subjects exhaled normally during the last repetition. The IOP was measured with an electronic tonometer during the fourth repetition in both modes while the subject sustained the exercise. Results: Mean IOP during exercise in mode I increased by 4.3±4.2 mm Hg (PϽ.001,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
114
1
17

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(139 citation statements)
references
References 18 publications
6
114
1
17
Order By: Relevance
“…17 Vieira et al noted that the average value of intraocular pressure is 15.5 mmHg with diurnal fluctuations of about 2.75 mmHg. 18 The mean increase in IOP observed in our study was slightly more than the diurnal fluctuations. Lid edema and chemosis was noted postoperatively in 20% of our patients, most of which subsided within the first 24 hours.…”
Section: Discussioncontrasting
confidence: 41%
“…17 Vieira et al noted that the average value of intraocular pressure is 15.5 mmHg with diurnal fluctuations of about 2.75 mmHg. 18 The mean increase in IOP observed in our study was slightly more than the diurnal fluctuations. Lid edema and chemosis was noted postoperatively in 20% of our patients, most of which subsided within the first 24 hours.…”
Section: Discussioncontrasting
confidence: 41%
“…Por outro lado, em outra investigação (9) foi mensurada a PIO, utilizando tonômetro eletrônico, de 30 homens (faixa etária entre 18 a 40 anos) todos com pressão intraocular > 21 mmHg e com ausência de glaucoma, os quais realizaram no exercício supino com quatro repetições a 80% de 1RM em dois modos: modo I (olho direito), com apnéia na última repetição e modo II (olho esquerdo), respiração normal durante a última repetição houve aumento da PIO. Contudo, no respectivo estudo o aumento da PIO foi maior no modo I comparado com o modo II.…”
Section: Discussionunclassified
“…Em exercícios em apnéia, situação frequentemente no TR, pode ocorrer aumento da PIO (9) , por outro lado em exercícios aeróbios, foi verificado o aumento da PIO em atletas do sexo masculino e não no feminino, e ainda não foi observado efeito sobre os homens sedentários, mas redução em mulheres sedentárias (7) . De fato, em sedentários submetidos a exercício agudo ocorreu diminuição da PIO a qual permaneceu baixa até 2 horas após a interrupção do exercício, diferente dos praticantes de exercícios que apresentam aumento da PIO imediatamente após o término do exercício e redução iniciando após 30 minutos do término (10) .…”
Section: Introductionunclassified
“…There is a gradual increase in blood pressure until exhaustion Occurs [7][8][9][10] . The current view is that the blood pressure set point is continuously regulated upward as long as the isometric exercise persists 11,12 . During isometric exercise, it has been demonstrated that blood pressure in the ophthalmic and brachial arteries rise in parallel.…”
Section: Discussionmentioning
confidence: 99%